Meta-Research: A comprehensive review of randomized clinical trials in three medical journals reveals 396 medical reversals - Herrera-Perez, Diana; Haslam, Alyson; Crain, Tyler; Gill, Jennifer; Livingston, Catherine; Kaestner, Victoria; Hayes, Michael; Morgan, Dan; Cifu, Adam S; Prasad, Vinay (eLife, 2019)
The ability to identify medical reversals and other low-value medical practices is an essential prerequisite for efforts to reduce spending on such practices. Through an analysis of more than 3000 randomized controlled trials (RCTs) published in three leading medical journals (the Journal of the American Medical Association, the Lancet, and the New England Journal of Medicine), we have identified 396 medical reversals. Most of the studies (92%) were conducted on populations in high-income countries, cardiovascular disease was the most common medical category (20%), and medication was the most common type of intervention (33%).
Keywords: low-value care; medical reversal; evidence-based medicine